Farm to Fork: EU’s Strategy for a Sustainable Food System - Giannou, Christina (HAPSc Policy Briefs Series, 2022)
The interrelationship of EU’s answer to the question of sustainable food systems is a pertinent issue when it comes to recognising the intrinsic relation amidst healthy people, societies, and a healthy planet. It is a strategy that is central in the EU Commission’s agenda, to reach the United Nations’ Sustainable Development Goals. It is paramount to understand the overall matrix of an agricultural and economic sustainable future, present and future goals calling out to members states for immediate need to help reshape sustainable solutions that will impact future generations. An outline of EU’s previous environmental framework will be examined comparatively to the current which pledges climate neutrality by 2050 binding this into Climate law. US President, Jo Biden in his first days in office ratified the Paris Agreement for a carbon free grid by 2035 and net zero emissions by 2050 reconvening US’s meaningful participation in the global climate network and, economic growth. Focus on key areas of study, environment, food, economy, future generations, and areas of reassessment will be viewed within the scope of shaping a perspective that the Green Deal and food sustainability is not only a call to reform previous economic models, but to address the elephant in the room; Can technologies guide us to a better future? Can they create new jobs? Provide better work opportunities? Support local farmers? Decrease food waste? Solve hunger? Save the planet? Is the Green Deal and Farm to Fork a utopia, a dream, or a sustainable reality?